Faktor-Faktor Yang Mempengaruhi Sticky Cost - Zul Azmi; Januryanti Januryanti (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to examine the factors that affect sticky cost. Specifically, this study examines the effect of sales, company size, asset intensity, and intellectual capital on sticky costs in industrial and consumer goods manufacturing companies listed on the Indonesia Stock Exchange. The research data consisted of 32 companies in the 2012-2017 period with 192 observations. Data were analyzed by multiple regression analysis. The results of this study indicate that the variable sales, company size, asset intensity, intellectual capital affect sticky cost. This research underlines that the company does not reduce costs related to intellectual capital despite a decrease in sales, but will try to find solutions through its resources to increase sales productivity. Thus, the company will need more costs because it will cause sticky costs.